Spin Flows in Magnetic Semiconductor/Insulator/Superconductor Tunneling Junction. (5th April 2015) - Kitamura, Michihide; Irie, Akinobu
Abstract : Tunneling currents along the c -axis of the majority and minority spin electrons have been studied for a magnetic semiconductor (MS)/insulator (I)/superconductor (S) tunneling junction consisting of a Ga1− x Mn x AsM S with x = 1/32, a nonmagneticI with a realistic dimension, and aH g Ba 2 Ca 2 Cu 3 O 8.4 (Hg-1223) high-T c S. The normalized charge and spin currents, Q T, C μ ′ V e x andQ T, S μ ′ V e x, and the flows of the majority↑ and minority↓ spin electrons, Q T, ↑ μ ′ V e x andQ T, ↓ μ ′ V e x, have been calculated at a fixed external voltageV ex, as a function of the magnetic moment μ ′ ( ≡ μ / μ B ) per a Mn atom which is deduced from the band structure calculations. It is found that the tunneling due to the minority spin electron dominates whenμ ′ < 2.4, but such a phenomenon is not found forμ ′ > 2.4 . We have pointed out that the presentM S / I / S tunneling junction seems to work as a switching device in which the ↑ and ↓ spin flows can be easily controlled by the external magnetic field.